Modelling and experimental validation of an EV torque distribution strategy towards active safety and energy efficiency. (15th January 2022) - Wei, Hongqian; Ai, Qiang; Zhao, Wenqiang; Zhang, Youtong
Abstract: Electric vehicles (EVs) have promisingly contributed to the decarbonization of the transportation sector. Torque distribution in energy management is vital to enhance EV safety and efficiency; however, its nonlinearity and real-time executability have not been extensively researched. This paper proposes an integrated torque distribution strategy that simultaneously considers vehicle security and dynamic power allocation. In the upper active safety layer, the yaw stability control and active front steering control are coupled to maintain vehicle stability. Additionally, a linear time-varying model predictive controller is developed to address the system nonlinearity and online executability problems. In the lower energy distribution layer, the motor efficiency and dynamic tire-slip power are simultaneously optimized to maintain EV energy conservation. Numerical simulations and hardware experiments are conducted in this study. The results demonstrate that the proposed integrated strategy is superior to other typical torque distribution strategies in terms of reducing the risk of emergent accidents. Moreover, the energy consumption of the powertrain is reduced by 13.4% and 14.2% under the steering and straight driving conditions, respectively. Overall, our study further promotes the practical application of EVs in the future automotive market and lays a solid foundation for intelligent torque distribution in autonomous EVs. Highlights: The integrated torque distribution strategy considering the active safety and energy distribution system is developed for the electric vehicles. The active front steering control and yaw stability control are coordinated to keep better maneuverability. The motor energy consumption and dynamical tire slip energy dissipation are both optimized. The research problems on the nonlinear tire saturation and online computational efficiency are addressed. The experimental test has validated the superiority of the proposed torque distribution strategy in a practical EV.